Correlation Between Home INR and Core Laboratory INR in Patients Supported with Continuous-Flow Left Ventricular Assist Devices. Issue 4 (July 2015) - Dionizovik-Dimanovski, Marija; Levin, Allison P.; Fried, Justin; Mody, Kanika P.; Simonich, Erica; Garan, Arthur Reshad; Yuzefpolskaya, Melana; Takayama, Hiroo; Naka, Yoshifumi; Colombo, Paolo C.; Kalesan, Bindu; Uriel, Nir; et al.
Abstract : It has been well established that patient self-testing (PST) of international normalized ratio (INR) using home monitoring devices increases the average therapeutic time and patient satisfaction. Long-term anticoagulation therapy with warfarin is used in patients with continuous-flow left ventricular assist device (CF-LVAD) to minimize the occurrence of thromboembolic events; however, PST devices have never been tested in patients with CF-LVADs. The purpose of this study was to determine the reliability of the PST device Alere INRatio 2 in patients supported with CF-LVADs. A correlation study was performed in 50 patients with CF-LVAD who were on stable warfarin therapy for a minimum of 3 weeks. Simultaneous INR values were determined from capillary whole blood samples using the Alere PST device and venous blood samples processed in the core laboratory at Columbia University Medical Center. There was a moderate correlation between the venous and the capillary INR values with a correlation coefficient of 0.83. The median difference between the methods was 0.39, with 44 of 50 patients recording higher INRs with Alere. Results remained unchanged after adjusting for use of amiodarone, abnormal hematocrit and liver enzymes, creatinine, and thyroid-stimulating hormone. Point of care testing with Alere correlates moderately well but consistently overestimates INR when compared with conventional laboratory testing in patients with CF-LVAD.